Usability of weather forecast to issue agromet advisory for Jammu district - SHARMA, VEENA; SINGH, MAHENDER; LOTUS, SONAM; SHARMA, B.C. (Journal of Soil and Water Conservation, 2024)
Weather manifests itself through its effects on soil, plant growth as well as on every phase of plant growth and development. A greater proportion of the total annual crop loss results from aberrant weather. Also crop disease are greatly influenced by weather. However, the crop losses can be reduced substantially by affecting adjustments through timely and accurate weather forecasts. The weather forecast and real time weather for Jammu district of UT of J&K was compared to assess the validity and Usability of weather forecast during 2019-20. The results indicated that highest value of usable forecast for rainfall (72.95%), maximum temperature (75.45%) & minimum temperature (71.34%) & RH maximum (89.38%) was found in post monsoon season. The usability of evening relative humidity (90.38) Cloud Cover (81.64%) and wind direction (34.65%) was found in the monsoon season. The usability of wind speed was 100% in pre-monsoon, post –monsoon and winter season followed by (98.38%) in monsoon season. The accuracy of weather forecast in advance is useful for farmers for doing appropriate field operations and crop management practices result in economic benefit of farmers by saving irrigations as well as preventing crop loss through insect pest attack.